The Importance of The Judicial Commission's Commitment in The Implementation of The State - Joko Sasmito; Erwin Owan HS; Bahtiyar Effendi (Faculty of Law, Universitas Pekalongan, 2022)
The judicial commission is an institution that has the authority and duty to uphold the dignity and honor of judges. Judges in carrying out their duties need to show high wisdom and ethics. For this reason, the judicial commission exists in order to help protect judges by supervising and controlling the behavior of judges. However, many judges and even supreme justices have been caught violating ethics and applicable law. This is an indication of less than optimal supervision and control of the judicial commission. Seeing this, researchers feel the need to see the importance of the commitment of the judicial commission in the administration of the state. In this study, researchers used the literature study method with books and journals as the main source and other relevant data as secondary data sources. The commitment of the judicial commission is very important for the administration of the state. The commitment of the judicial commission will make the judicial commission better in supervising and controlling the behavior of judges. This commitment will also assist the judicial commission in overcoming pressure, solicitation of collusion, and even threats from outside in carrying out its duties.Keyword: Juicial Cmmission, Administration of the State, Cmmitment, Pulic trust, Judicial Ititution